ANALISIS KELAYAKAN USAHA JAMUR TIRAM DI DESA MPANAU KECAMATAN BIROMARU KABUPATEN SIGI - Farhah, Farhah; Laapo, Alimudin; Howara, Dafina (AGROTEKBIS, 2017)
This study aims to determine the feasibility of revenue and oyster mushrooms in the village of the District Mpanau Biromaru Sigi. The research was conducted on oyster mushroom businesses located in the village of the District Mpanau Biromaru Sigi. Respondents consisted of 1 employee that business owners oyster mushrooms. The results showed that the income earned on oyster mushroom business in October IDR. 2,217,732 oyster mushroom businesses gain and deserve to be developed with a value of R/C of 1.73 indicates that any expenditure of IDR. 1.00 will earn revenue of IDR. 1.73.Â Key Words : Feasibility Analysis, Oyster Mushroom, Village Mpanau.